The Effect of Financial Performance on The Share Price of The Indonesian Sharia Stock Index 2019 - 2024 - Razak, Keenan M; Wijayanti, Rahma (Airlangga Journal of Innovation Management, 2025)
The purpose of this research was to determine the return on capital, company growth, company size, and profitability on firm value. The quantitative method used meets the principles of systematicity, rationality, and scientific objectivity. This study makes it easier for investors to evaluate a Sharia company in Indonesia. Annual financial statements and stock price data are the secondary data used.  Statistical software is used to perform multiple linear regression analysis. Data analysis uses multiple regression test analysis tools. This study selected 20 Islamic companies with the largest market capitalization among other companies listed on the Indonesian Sharia Stock Index (ISSI), as shown in the ISSI data in 2025. This research is based on the assumption that companies with large market capitalization have a significant influence on market dynamics and provide a more accurate picture of the relationship between Islamic and conventional businesses. Financial ratios such as Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) are the independent variables in this study, and the annual stock price of each company is the dependent variable. The results show that ROA and DER greatly affect stock prices.  The results show that investors in the stock market are more willing to invest.